The The Change of Nutrients Rations Quality of Feed Fermented with Different Moisture Content - Miksusanti Miksusanti; Sofia Sandi; Fitra Yosi; Eli Sahara; Nasir Rofiq (Indonesian Journal of Environmental Management and Sustainability, 2019)
ABSTRACT The change of nutrients on rations made from local raw materials was evaluated after being fermented in various moisture contents. The experiment used completely randomized design comprise of 5 treatments and 3 repetitions. The treatments were P0 (fermentation without moisture), P1, P2, P3 and P4 (fermentation in 40%, 50%, 60% and 70% moisture content). Variables observed were total microbe, total acid, acidity (pH) and the change of dried matter content, organic matter, crude protein, crude lipid, crude fiber and Nitrogen-free extract. The result showed that there are statistically significance differences (P<0.05) between local raw materials rations fermented in different moisture contents towards variables observed. Local raw materials rations fermented in 50% moisture content exhibited good nutrients quality indicated by increased in dried matter content, organic matter, crude protein, Nitrogen-free extract, total microbe and total acid while crude lipid, crude fiber and acidity (pH) showed a decreased.